PTPN21 Overexpression Promotes Osteogenic and Adipogenic Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells but Inhibits the Immunosuppressive Function - Huafang Wang; Xiaohang Ye; Haowen Xiao; Ni Zhu; Cong Wei; Xiang Sun; Limengmeng Wang; Binsheng Wang; Xiaohong Yu; Xiaoyu Lai; Shan Fu; He Huang (Hindawi Limited, 2019)
Protein tyrosine phosphatases (PTPs) act as key regulators in various cellular processes such as proliferation, differentiation, and migration. Our previous research demonstrated that non-receptor-typed PTP21 (PTPN21), a member of the PTP family, played a critical role in the proliferation, cell cycle, and chemosensitivity of acute lymphoblastic leukemia cells. However, the role of PTPN21 in the bone marrow microenvironment has not yet been elucidated. In the study, we explored the effects of PTPN21 on human bone marrow-derived mesenchymal stem cells (BM-MSCs) via lentiviral-mediated overexpression and knock-down of PTPN21 in vitro. Overexpressing PTPN21 in BM-MSCs inhibited the proliferation through arresting cell cycle at the G0 phase but rendered them a higher osteogenic and adipogenic differentiation potential. In addition, overexpressing PTPN21 in BM-MSCs increased their senescence levels through upregulation of P21 and P53 and dramatically changed the levels of crosstalk with their typical target cells including immunocytes, tumor cells, and vascular endothelial cells. BM-MSCs overexpressing PTPN21 had an impaired immunosuppressive function and an increased capacity of recruiting tumor cells and vascular endothelial cells in a chemotaxis transwell coculture system. Collectively, our data suggested that PTPN21 acted as a pleiotropic factor in modulating the function of human BM-MSCs.